MO451GUANIDINYLATED APOLIPOPROTEIN C3 (APOC3) A NOVEL PLAYER IN CKD AND CKD-ASSOCIATED CARDIOVASCULAR DISEASES. (29th May 2021) - Schunk, Stefan; Hermann, Juliane; Sarah, Triem; Lellig, Michaela; Hahm, Eunsil; Boor, Peter; Reiser, Jochen; Jankowski, Joachim; Fliser, Danilo; Jankowski, Vera; Speer, Thimoteus
Abstract: Background and Aims: Cardiovascular diseases (CVD) and chronic kidney diseases (CKD) are highly prevalent in Western populations and account for a substantial proportion of mortality. We found that apolipoprotein C-3 (ApoC3), a constituent of triglyceride-rich lipoproteins, induces alternative NLRP3 inflammasome activation in human monocytes and thus causes sterile inflammation. The aim of the present study was to screen ApoC3 for the presence of posttranslational protein modifications and to assess its relevance in vitro, in vivo, as well as in a prospective cohort of CKD patients. Method: ApoC3 was subjected to proteomic analysis. The proinflammatory properties of ApoC3 were assessed in human monocytes and in humanized mice. Moreover, posttranslationally modified ApoC3 was quantified in prospective cohort of 543 patients with various etiologies of CKD and linked to kidney and cardiovascular outcomes. Results: We identified posttranslational guanidinylation of lysine residues of ApoC3 (gApoC3) in patients after acute myocardial infarction and in patients with CKD. gApoC3 accumulates in kidneys and hearts after injury as determined by 2D-proteomic analyses. In human monocytes, guanidinylation enhanced the binding of ApoC3 to the cell surface and exerted substantially stronger pro-inflammatory effects as compared native ApoC3. In humanized mice, gApoC3 strongly induced kidney fibrosis and abolished the regeneration after vascular injury. In a prospective clinical trial of 543 patients, higher gApoC3 blood levels as determined by mass spectrometry were associated with increased mortality as well as cardiovascular and renal events during a long-term follow-up. Conclusion: The present study provides evidence from preclinical models and a prospective clinical trial that gApoC3 plays an important role in the development of organ injury in patients with CKD, myocardial infarction and other clinical conditions. The clinical study represents one of the largest trials, in which the association of a specific PTM and clinically relevant outcomes was assessed. These findings highlight gApoC3 as a pathophysiologically relevant factor in development of organ dysfunction.